2012
DOI: 10.2172/1064405
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Geological Carbon Storage Options in the Illinois Basin: Validation Phase

Abstract: The Midwest Geological Sequestration Consortium (MGSC) assessed the options for geological carbon dioxide (CO 2) storage in the 155,400 km 2 (60,000 mi 2) Illinois Basin, which underlies most of Illinois, western Indiana, and western Kentucky. The region has annual CO 2 emissions of about 265 million metric tonnes (292 million tons), primarily from 122 coal-fired electric generation facilities, some of which burn almost 4.5 million tonnes (5 million tons) of coal per year (U.S. Department of Energy, 2010). Val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In the Illinois natural gas storage fields, the St. Peter Sandstone has excellent reservoir quality with porosity values of 5% to over 25% (average 14-16%) and permeability from 10 mD to over 1000 mD (average 150-400 mD). Maquoketa shale acts as a primary confining seal with average porosity determined using mercury injection of 0.9% and permeabilities near 1.8 × 10 −4 mD, indicating its effectiveness as a barrier to vertical migration of fluids [47].…”
Section: Case Study Detailsmentioning
confidence: 99%
“…In the Illinois natural gas storage fields, the St. Peter Sandstone has excellent reservoir quality with porosity values of 5% to over 25% (average 14-16%) and permeability from 10 mD to over 1000 mD (average 150-400 mD). Maquoketa shale acts as a primary confining seal with average porosity determined using mercury injection of 0.9% and permeabilities near 1.8 × 10 −4 mD, indicating its effectiveness as a barrier to vertical migration of fluids [47].…”
Section: Case Study Detailsmentioning
confidence: 99%
“…The results revealed that 0.387 tonnes of CO 2 were sequestrated, which was very low compared with the predicted one from the Langmuir isotherm. 143,144 Besides that, a pilot test was conducted in the Central Appalachian Basin, United States, in which 907.185 tonnes of CO 2 were injected at a rate of 36−45 tonnes per day in the initial days and then later decreased to 20 tonnes per day at a maximum injection pressure of 6.9 MPa. It was revealed that 65% of injected CO 2 was stored.…”
Section: Field Applicationsmentioning
confidence: 99%